Contextual hypermedia glosses for facilitating English vocabulary acquisition and reading comprehension at a university of technology - Wissing, Gerrit-Jan (North-West University (South Africa) , Potchefstroom Campus, 2017)
This study investigated the usefulness of non-linear lexical hypermedia glosses for supporting English Second Language vocabulary acquisition and reading comprehension where glosses are integrated into electronic reading materials. Mayer’s Cognitive Theory of Multimedia Learning was the theoretical framework guiding the study. A hypermedia glossing system was developed for the study and embedded in the virtual learning environment in use at the Tshwane University of Technology. A Solomon four group experimental research design was used. The glossing system was deployed in a comprehension test administered electronically to the treatment groups. The control groups did not have glossing support available. The 415 participants in this study were drawn from the foundation programmes of the Faculty of Engineering and the Built Environment. Three data collection instruments were developed to collect data. All the participants completed a text-specific vocabulary test administered directly before, directly after and eight weeks after the treatment. They also completed the reading comprehension test, and 212 participants from the treatment groups completed a user experience survey. The survey was used to determine the perceived usefulness of hypermedia glosses for vocabulary acquisition and reading comprehension. The study found no practically significant effect of glossing on vocabulary when measured either immediately after or eight weeks after the treatment. There was also no practically significant effect on reading comprehension. Neither the pre-test, nor the interaction of the pre-test on the treatment, had a practically significant effect on vocabulary learning or reading comprehension. Participants perceived the glosses to be useful for vocabulary acquisition and reading comprehension, with significant correlation between different aspects of perceived usefulness. This perception of usefulness of glossing was however not reflected in practically significant effects on estimated group mean scores for the text-specific vocabulary tests and reading comprehension test used in the study. Making hypermedia glosses available for readers of academic texts is recommended, especially since readers perceive them to be useful, and they make their reading experience enjoyable. Language level of definitions should closely match the language ability of readers. Future research should be conducted under conditions where test anxiety is limited. A system for tracking gloss access should be used, so that gloss access can be matched to test performance on an individualised basis. Hierdie was ‘n ondersoek na die bruikbaarheid van nie-lineêre leksikale hypermedia-glosse om woordeskat en leesbegrip in Engels as Tweede Taal te ondersteun. Mayer se Kognitiewe Teorie vir Leer met Multimedia was die teoretiese raamwerk wat rigting aan die studie gegee het. ‘n Hipermedia-glosseringstelsel is ontwikkel vir die studie. Dié is geïntegreer in die virtuele leeromgewing wat by die Tshwane Universiteit vir Tegnologie gebruik word. ‘n Solomon vier-groep eksperimentele navorsingsontwerp is gebruik. Die glosseringstelsel is ontplooi in 'n begripstoets wat elektronies aan die toetsgroepe bedien is. Glossering was nie vir die kontrolegroepe beskikbaar nie. Die 415 deelnemers aan hierdie studie was afkomstig uit die grondslagprogramme van die Fakulteit Ingenieurswese en die Beboude Omgewing. Drie dataversamelingsinstrumente is ontwikkel om data in te samel. Al die deelnemers het 'n teks-spesifieke woordeskat-toets direk vóór, direk ná en agt weke ná die behandeling voltooi. Hulle het ook die leesbegripstoets gedoen, en 212 deelnemers uit die behandeling-groepe het 'n gebruikerservaring-opname voltooi. Die opname is gebruik om deelnemers se persepsie van die nutswaarde van hypermedia-glosse vir woordeskat-verkryging en leesbegrip te bepaal. Woordeskat is onmiddellik en agt weke na die behandeling gemeet, maar geen prakties betekenisvolle effek van glossering is gevind nie. Daar was ook geen prakties betekenisvolle effek op leesbegrip nie. Nóg die voortoets, nóg die interaksie van die voortoets op die behandeling het 'n prakties betekenisvolle effek op woordeskat of leesbegrip gehad nie. Deelnemers het die glosse as nuttig vir woordeskatverkryging en leesbegrip geag, met 'n beduidende korrelasie tussen verskillende aspekte van nutswaarde. Hierdie persepsie van nutswaarde is egter nie weerspieël in prakties betekenisvolle effek op geskatte gemiddelde groeptellings vir die teks-spesifieke woordeskattoetse en leesbegripstoets wat in die studie gebruik is nie. Hipermedia-glossering behoort beskikbaar gestel te word vir lesers van akademiese tekste, veral aangesien lesers hulle nuttig ag, en dit hul leeservaring aangenaam maak. Die taalvlak van definisies moet so nou moontlik ooreenstem met die taalvaardigheid van lesers. Toekomstige navorsing behoort uitgevoer te word onder omstandighede waar toetsangs beperk word. 'n Naspoorstelsel vir glos-raadpleging behoort gebruik te word, sodat raadpleging op 'n individuele basis aan toetsprestasie gekoppel kan word.
PhD (Curriculum Development), North-West University, Potchefstroom Campus, 2017
Keywords: Cognitive Theory of Multimedia Learning; English Second Language; Hypermedia Glossing; Perceived usefulness; Reading comprehension; Second language learning; Solomon Four Group design; Technology Enhanced Learning; Vocabulary acquisition; Kognitiewe Teorie vir Leer met Multimedia; Engels as Tweede Taal; Hipermedia-glossering; Geagte nutswaarde; Leesbegrip; Tweede taal leer; Solomon Vier-groep ontwerp; Tegnologie-verrykte Leer; Woordeskatverkryging